Employers’ experience in managing high potential employees in Malaysia - Juhdi, Nurita (2013)

(untitled)
The main objective of the survey was to study the practices in high potential (HIPO) employee development in Malaysia. HIPOs are the organization’s top performers in their current jobs and have the potential to move up to higher positions and more challenging responsibilities. The respondents of the study were in the positions of company CEOs, HR managers and line managers from various industries. All data were collected using survey forms. A total of two hundred and sixty forms were collected back but twenty three forms were poorly answered. As a result, only two hundred and thirty seven forms were useful for further analyses. The findings indicated that employers put highest emphasis on employees who were customer service oriented and able to create high performing teams. Given dynamic business environment that is always driven by high expectations from customers, companies need employees who are able to anticipate changes and be proactive in dealing with changing customers’ expectations. In terms of methods used to identify high potential employees in organizations, the most common method was performance appraisal by immediate superiors and the least common method was nomination method. Two most common methods to develop high potential employees were job enlargement and executive development programs and the least used was executive MBA program. The study also revealed that the most common problem in high potential employee development programs was in dealing with those who had problems in balancing personal and work life balance. Generally the respondents indicated their high potential employee development programs as effective. The findings also revealed that the effort in identifying high potential employees was consistent with the amount of development programs provided.